Comparison of Stapler, Single Layer and Double Layer Techniques for Colon Closure in Dogs - Amir Nawas Khan; Allah Bux Kachiwal; Shahla Karim Baloch; Rameez Raja Kaleri; Khalid Hussain Khan; Muhammad Zib; Faisal Noor Qureshi; Ghulam Murtaza Mari; Muhammad Saleem Pahnwar; Rashid Ali Shah; Abdullah Marri (Journal of Basic & Applied Sciences, 2017)
The present study was performed on 18 healthy dogs (aged 16.80±1.22 months) and body weight (17.07± 2.21 kg) to determine the best suturing technique among single layer, double layer and stapler technique for the closure of colon in dogs. All dog were divided into three groups, placing 6 animals in each group, i.e. group A was closed with single layer suture technique, group B was closed with double layer suture technique and group C was closed with stapler technique. The number of stitches required for colon closure were 8.83, 16.33 and 9.16 in groups –A, B and C respectively. The mean number of stitches and time taken for the completion of double layer technique was significantly higher (P<0.01) than single layer and stapler techniques. The mean of total duration of abdominal closure was 47.00, 45.16 and 34.83 minutes in group A, B and C respectively. The mean of total duration for surgery was 57.16, 64.50 and 46.33 minutes in group A, B and C respectively..The study reveals that all the techniques were not completely free from complications and advantages. Although stapler technique had some advantages like minimal adhesion between anastomotic line and other structures, higher bursting wall tension at operated site and less duration required for closure of anastomosis. It is concluded that stapler technique used in this study proved better than single layer and double layer suture techniques in dogs.